Effect of Using Coconut Fiber to Increase Strength and Modulus of Elasticity in Asphaltic Concrete Mixes - Salim Salim; Wisnumurti Wisnumurti; Agung Sugeng Widodo; Hanafi Ashad (Jurnal Civil Engineering Study)
The modulus of elasticity or modulus of stiffness is a metric that indicates the stiffness of a mixture based on the stress and strain relationship. One very important component that influences the performance of asphalt pavement is the stiffness modulus. A lower stiffness modulus value makes it easier to experience deformation, which causes the pavement to crack easily when subjected to heavy loads. Asphalt concrete mixtures with high stiffness modulus values ​​will be stiffer and more resistant to deflection. This study is experimental with the aim of obtaining an asphalt concrete mixture that is able to withstand loads without changes. In this study, the asphalt concrete mixture was composited with coconut fibers with the aim of determining the effect of coconut fibers in increasing stress and tensile strain as well as the stiffness modulus of the mixture. This type of test is carried out using an ITS test equipment to obtain stress, strain and stiffness modulus values.